Implementation of The Strengthening Pancasila Student Profile Project Through Entrepreneurship - Kurniati, Hera; Disman (International Conference on Elementary Education, 2025)
Pancasila Student Profile is a concept developed in the education curriculum in Indonesia to shape student character and competence. Entrepreneurship is a program aimed at developing student character. Within the scope of education, students must always be directed to change themselves through a creative and innovative spirit through quality superior programs. At the elementary school level, this concept becomes important in applying entrepreneurship to create superior competitive people. This research aims to implement and strengthen the Pancasila Student Profile Project through the theme of entrepreneurship in schools. This project is expected to develop character, and skills and instill an entrepreneurial spirit in students. The research subjects were carried out on fifth-grade students at one of the Bandung City State Elementary Schools with 27 students. The method used is a qualitative approach with data collection techniques in the form of interviews and observations. The research results show that the implementation of the project to strengthen the profile of Pancasila students through the theme of entrepreneurship can encourage students to be creative, and foster a leadership spirit and entrepreneurial spirit. Apart from that, students also show a better understanding of Pancasila values in the context of everyday life. Thus, this project not only contributes to the development of entrepreneurial competence but also strengthens national identity and character among the younger generation. This research recommends implementing similar methods in various schools to support sustainable character education.